Analysis of Health Promotion Program Implementation in Hospital - Bambang Setiaji; Satria Nandar Baharza; Afriada Noor Fathoni (GLOBAL HEALTH SCIENCE GROUP, 2021)
Hospital must make efforts to improve the ability of patients, clients, and community groups, so that patients can be independent in accelerating healing and rehabilitation. The purpose of this study was to know in depth about the evaluation of the implementation of PKRS program at Sukadana Regional General Hospital. The type of this research is qualitative and the results of the study are presented in description. Subjects or informants were taken by purposive sampling. The number of informants is 8 people, Deputy Director of Sukadana Hospital, Human Resource Quality and Development Section, Maintenance of Facilities and Infrastructure Section, Hospital Managers, PKRS Coordinators, Heads of Rooms, and Hospital Visitors. Data collection techniques using in-depth interviews and observations, Data analysis is carried out by organizing the data obtained into a category, describing the data into units, analyzing important data, compiling or presenting data in accordance with the research problem in the form of conclusions that are easy to understand. Based on in-depth interviews with 8 informants there are 3 factors that influence the success of the Health Promotion program at the Hospital, namely input indicators (Commitment of Directors and All Staffs, Health Promotion in Hospital trained personnel, Health Promotion in Hospital Management, Funds Budget, Facilities and Infrastructure), Process indicators (Health Promotion in Hospital Activities Inside and Outside the Building), output indicators (Health Promotion in Hospital Activity Coverage), and output indicators (Hospital Visitor Knowledge). There is still a need for commitment between the hospital director and all staff, the allocation of funds is still insufficient for the implementation of Health Promotion in Hospital and the finding of facilities and infrastructure that support the implementation of Health Promotion in Hospital